APLIKASI ON FARM RESEARCH TEKNOLOGI MIKRONUTRISI UNTUK MENINGKATKAN PENDAPATAN RUMAH TANGGA ANGGOTA KELOMPOK TANI - Heri Dwi Putranto; Yossie Yumiati; Novitri Kurniati (DHARMA RAFLESIA, 2018)
Cattle has been widely captived as a livestock in Indonesia. Unfortunately, eventhough the Ministry of Agriculture Republic of Indonesia launched a national program called Program Swasembada Daging Sapi dan Kerbau since 2014, the program result did not reach as high as targeted. Previous IbM program cooperated with Warga Rukun II Farmers Group located at Lokasi Baru Village, Air Periukan District, Seluma Regency, Bengkulu Province. Based on result of on farm research applied in site, the treatment of micronutritional supplemen (3 %) on cattles was feasible to be applied and it gave farmers a household income improvement. Keywords: farmers group, household income, micronutritional technology